Neovascular age-related macular degeneration without exudative recurrence over 24 months after initial remission - Han Joo Cho; Young Joon Jeon; Wontae Yoon; Jihyun Yoon; Jaemin Kim; Jong Woo Kim (Scientific Reports, 2022)
Abstract We investigated the characteristics of neovascular age-related macular degeneration (AMD), which rarely recurs after initial remission. This study retrospectively analyzed 392 neovascular AMD patients treated with anti-vascular endothelial growth factor (VEGF). All patients received three monthly loading doses of anti-VEGF injections, followed by a pro re nata (as needed) regimen for 24 months. The baseline characteristics associated with the odds of having no recurrence within 24 months were evaluated using multivariate modeling. After the initial three loading injections over 24 months, 58 (14.8%) eyes showed no exudative recurrence and did not require additional anti-VEGF injections. These patients without exudative recurrence had significantly better best-corrected visual acuity (P = 0.003) and lower central subfoveal thickness (P = 0.035) at 24 months than those with exudative recurrence. Additionally, the incidence of macular atrophy was significantly lower in the former than in the latter (8.6% vs. 21.9%; P = 0.020). Multivariate analysis revealed that younger age (odds ratio [OR], 0.901; P = 0.033), smaller lesion size (OR, 0.589; P = 0.016), and absence of fibrovascular pigment epithelial detachment (PED) (OR, 1.349; P = 0.028) were associated with higher odds of no recurrence during follow-up. Approximately 15% of the neovascular AMD patients showed no exudative recurrence after initial remission during the 24-month follow-up. The infrequent recurrence after initial remission correlated with younger age, smaller lesion size, and absence of fibrovascular PED.